2021
DOI: 10.1186/s12940-021-00770-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particle levels measured on board short-haul commercial passenger jet aircraft

Abstract: Background Airline crew members report adverse health effects during and after inhalation exposure to engine oil fumes sourced to the air supply system onboard commercial and military aircraft. Most investigations into the causal factors of their reported symptoms focus on specific chemical contaminants in the fumes. The adverse health effects reported in aircrew exposed to the aircraft air supply, bled unfiltered off the engine or Auxiliary Power Unit (APU) may be related to particulate exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Ultrafine Particles are generated when the oils are exposed to high temperatures in the engine or APU [ 70 , 74 - 76 ]. Oil contamination of the bleed air results in large increases in UFPs with peak concentrations in the 40–80 nm range [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafine Particles are generated when the oils are exposed to high temperatures in the engine or APU [ 70 , 74 - 76 ]. Oil contamination of the bleed air results in large increases in UFPs with peak concentrations in the 40–80 nm range [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the authors report occupational exposures to ultrafine particles as high as 10 6 –10 7 particles per cm 3 . Notably, Michaelis et al [ 60 ] recently showed that values for the in-cabin measurement of UFP can vary in the order of 10 4 to 10 5 particles/cm 3 . Ren et al [ 61 ] demonstrated that the in-cabin values were highly related to the take-off operations in airplanes waiting, before departure, in areas downwind the take-off area.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increased attention on the presence and potential health impact of elevated levels of ultrafine particles (UFP; PM0.1) in the bleed air supplied to the cabin and flight deck on commercial aircraft. 9,10,11,12 In the methodology section, Chen et al…”
Section: E Xp Osure To Re S Pir Ab Le Parti Cle S and Ufp Wa S Only C...mentioning
confidence: 99%
“…13 Notably, though, a World Health Organization guideline defines a count of >20 000 particles/ cm 3 (1 h mean) as "high", 14 which is considerably lower than some of the aircraft data. 9,12,15…”
Section: E Xp Osure To Re S Pir Ab Le Parti Cle S and Ufp Wa S Only C...mentioning
confidence: 99%